The White Snake and other Stories - Mordi, Sigrid (Evans Brothers (Nigeria Publishers) Ltd, 1981)
This book is a collection of delightful children's stories of a contemporary nature. The stories in this collection is aimed at enabling the child to identify himself situationally.
Keywords: Fairytales